The Influence of Local Government Size, Legislative Size, and BPK Audit Opinion on Local Government Financial Performance - Putri, Ria Dwi; Hendaris, Raden Budi (E-Jurnal Akuntansi; Vol 35 No 6 (2025), 2025)
Regional financial performance is measured through the independence ratio which reflects the ability of regional autonomy. However, the low independence ratio in most regions indicates that regional autonomy has not been running optimally. This study is intended to obtain empirical evidence regarding the influence of Local Government Size, Legislative Size and BPK Audit Opinion on the Financial Performance of Local Government. The data used is secondary data from the www.jabar.bps.go.id and www.jabar.bpk.go.id of 2019-2023. The population in this study was determined through census techniques covering 18 districts and 9 cities in West Java Province. The data analysis method used multiple linear regression with IBM SPSS 27 software. The results of this study prove that the Size of the Regional Government has a significant positive effect on the Financial Performance of the Regional Government. Legislative size have a significant negative effect on the Financial Performance of Local Governments. And BPK Audit Opinion does not have a significant effect on the Financial Performance of Local Governments. Keywords: Size of Local Government; Legislative Size; BPK Audit Opinion; Local Government Financial Performance